ВОКАЛЬНАЯ МУЗЫКА (ART AND CULTURE BULLETIN, 2024)
It is known that these unique customs and national heritages, like all the peoples andnations of the world, have been passed down from father to son, from generation to generation. Thesetraditions include teacher-student traditions: folk songs, folk tales, open and cheerful epics, and many folksongs.
Keywords: note; performance technique; music; individual performance; soloist; national musical instrument.